Phase 1b Study to Evaluate Safety, Tolerability, and Maximum Tolerated Dose of PF-05230907 for Intracerebral Hemorrhage. Issue 1 (January 2021) - Silva Blas, Yolanda; Diringer, Michael N.; Lo, Benjamin; Masjuan, Jaime; Pérez de la Ossa, Natalia; Cardinal, Matthew; Yong, Florence; Zhu, Tong; Li, Gang; Arkin, Steven
Abstract : Background and Purpose: This study aimed to determine the maximum tolerated dose and to evaluate the overall safety and tolerability of single doses of PF-05230907 in subjects with acute intracerebral hemorrhage. Methods: Individuals presenting with intracerebral hemorrhage were enrolled in a phase 1, multicenter, open-label clinical trial. A Bayesian modified continual reassessment method design based on treatment-emergent thromboembolic or ischemic events was adopted. Sequential dosing, an external data monitoring committee, and prespecified stopping rules were incorporated as safeguards. Results: Twenty-one subjects received PF-05230907. The mean (±SD) age in years and intracerebral hemorrhage volume in mL at baseline were 62 (±9) and 18 (±11), respectively. Two treatment-emergent thromboembolic or ischemic events occurred (deep vein thrombosis and cerebral ischemia), in the 30 μg/kg dose group. There were no other clear drug-related toxicities at dose levels ranging from 5 to 30 μg/kg. At the time of study termination, the maximum tolerated dose was estimated to be 24 μg/kg, with a mean fitted dose-toxicity estimate of 11.9% (95% CI, 1.2%–27.4%). Conclusions: Single doses of PF-05230907 appeared to be tolerated across a range of doses in the intracerebral hemorrhage population, with thrombotic events observed only at the highest dose level tested. Recruitment within the recommended therapeutic window of opportunity remains a challenge. Registration: URL: https://www.clinicaltrials.gov . Unique identifier: NCT02687191. Abstract : Supplemental Digital Content is available in the text.